PPM ANGKRINGAN SATE AYAM - Mei - Indrawati; Woro Utari; Chamariyah Chamariyah; Risca Ayu Rachmania; Kresensia Darmawati (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
This Community Service program partner, Mrs. Jama'li, who is in the chicken satay business, is located in Lontar Village, Sambikerep District, Surabaya City. Problems faced by partners: 1) Packaging that still sees oil seeping from the spices; 2) The absence of financial records; 3) The absence of production planning; 4) There is no wider marketing effort; 5) The determination of the selling price has not been calculated correctly; 6) Cleanliness; and 7) Production equipment (fans) are obsolete. Solutions offered: training and assistance: 1) packaging; 2) financial management; 3) production planning; 4) product marketing; 5) determination of selling price; 6) sanitation; and 7) procurement of fans. The results of the activity: the implementation of training and mentoring 1) good packaging, now there is no longer visible seepage of spices in the package; 2) financial management, partners are able to make records of expenses and income from their business; 3) production planning, partners can begin to reduce the number of unsold satays; 4) product marketing, partners are already using online marketing; 5) determining the selling price of the product, partners can calculate the cost of production and consider the price of satay competitors; 6) sanitation, partners pay attention to the cleanliness of products, tools and places of business; and 7) a new fan is available. Mitra was able to increase the number of satays sold from 100 skewers to 200 skewers per day.